Image Analysis in Earth Sciences Microstructures and Textures of Earth Materials - Heilbronner, Renée; Barrett, Steve (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Image Analysis in Earth Sciences is a graduate level textbook for researchers and students interested in the quantitative microstructure and texture analysis of earth materials. Methods of analysis and applications are introduced using carefully worked examples. The input images are typically derived from earth materials, acquired at a wide range of scales, through digital photography, light and electron microscopy. The book focuses on image acquisition, pre- and post-processing, on the extraction of objects (segmentation), the analysis of volumes and grain size distributions, on shape fabric analysis (particle and surface fabrics) and the analysis of the frequency domain (FFT and ACF). The last chapters are dedicated to the analysis of crystallographic fabrics and orientation imaging. Throughout the book the free software Image SXM is used.